Characteristics of virulence of Puccinia triticina populations and the potential of the Lr24, Lr25, LrSp genes for spring common wheat breeding in the Southern Ural - V. A. Tyunin; E. R. Shreyder; E. I. Gultyaeva; E. L. Shaydayuk (Вавиловский журнал генетики и селекции)
Monitoring of pathogen populations is important for successful genetic wheat protection against leaf rust and identification of pathotypes with virulence to the resistance genes used. The aim of this work was analysis of Puccinia triticina populations in the Chelyabinsk region for virulence and studying the effectiveness of Lr-genes at the field for improving and stabilization of genetic protection from wheat leaf rust in the Southern Urals. Infection materials were collected in the experimental field of the Сhelyabinsk Research Institute of Agriculture from breeding lines, commercial and perspective wheat varieties in 2014–2016. In total, 383 single pustule isolates were studied: 180 in 2014, 131 in 2015, and 72 in 2016. The Lr24 gene was characterized as highly effective. The single isolate virulent to ТсLr19 line was revealed only in 2014. Isolates virulent to the Lr9 gene occurred annually both on the varieties carrying this gene and those without it, and all of them were characterized by avirulence to the Lr26 gene. According to the Nei index (N), no significant differences in virulence were revealed between Chelyabinsk populations in 2014–2016. 27 virulence phenotypes were determined using 20 TcLr-lines. The phenotypes TQTTR and TGTTR avirulent to lines ТсLr19, ТсLr24, ТсLr26 and ТсLr9, ТсLr19, ТсLr24, ТсLr26, respectively, were common in 2014–2016. The results on the effectiveness of Lr-genes at the seedling stage correlated with estimates for Thatcher Lr-lines, breeding materials and varieties with known Lr-genes grown at the field on the breeding nursery of the Сhelyabinsk Research Institute of Agriculture. The highly effective genes Lr24, Lr25, Lr28, Lr29, Lr37 and some others were found to have promise for use in wheat breeding in the Ural. The use of these genes and combination of these genes with non-effective ones will allow the genetic diversity of new wheat varieties to be increased and the fungus populations to be stabilized. By now, at the field conditions in the Ural region, the effective combinations of Lr-genes revealed are Lr9+Lr19, Lr9+Lr26, Lr9+Lr37, Lr9+Lr10+Lr26, and Lr9+Lr26+Lr37.